Methods and Tools of Parallel Programming Multicomputers Second Russia-Taiwan Symposium, MTPP 2010, Vladivostok, Russia, May 16-19, 2010, Revised Selected Papers - Hsu, Ching-Hsien.; Malyshkin, Victor. (Lecture Notes in Computer Science, 2010)
It is our great pleasure to present the proceedings of the second RussiaỚ<U+001c>Taiwan Symposium on Methods and Tools of Parallel Programming (MTPP 2010). MTPP is the main regular event of the RussiaỚ<U+001c>Taiwan scientific forum that covers the many dimensions of methods and tools of parallel programming, algorithms and architectures, encompassing fundamental theoretical approaches, practical experimental projects, and commercial components and systems. As applications of computing systems have permeated every aspect of daily life, the power of computing systems has become increasingly critical. Therefore, MTPP is intended to play an important role allowing researchers to exchange information regarding advancements in the state of the art and practice of IT-driven services and applications, as well as to identify emerging research topics and define the future directions of parallel computing. We received a large number of high-quality submissions this year. In the first stage, all papers submitted were screened for their relevance and general submission requirements. These manuscripts then underwent a rigorous peer-review process with at least three reviewers per paper. At the end, 33 papers were accepted for presentation and included in the main proceedings. To encourage and promote the work presented at MTPP 2010, we are delighted to inform the authors that some of the papers will be accepted in special issues of the Journal of Supercomputing, which has played a prominent role in promoting the development and use of parallel and distributed processing.